Grundzüge der jungtertiären Geomorphogenese der mittleren Anden - Fischer, Klaus (ERDKUNDE, 1985)
Already at the beginning of the late Tertiary the middle section of the Andes showed a hilly to mountainous topography with large intra-Andean accumulation areas. Although it has been postulated several times, there is no evidence of a peneplain covering the area, and especially so in the case of the ranges of the Argentinian and Chilean Puna. Furthermore, it is impossible to reconstruct from the geomorphology of the area a phased development of the mountains to their present shape during the Neogene as has been and still is maintained by geologists especially as a consequence of tectonic cycles. The middle section of the Andes did not reach its present heights before the Miocene and Pliocene. Preserved fossil landforms are to be dated as being rather young (Pliocene/Pleistocene), although not of identical age. Finally, there is no indication as to a radical climatic-geomorphological change during the development of the mountains.